Structural Studies on Metal Complexes of Benzthienoin Oxime - Mehta, B.H.; Dixit, P.M. (Asian Journal of Chemistry, 2010)
Mn(II), Pe(II), Co(II), Ni(II), Cu(II), Zn(II), Pd(II) and Mo(VI) complexes have been prepared by reacting metal salts with the ligand benzthienoin oxime in alcoholic medium. All the complexes are coloured crystalline solids and are non-electrolytes in nitrobenzene. Elemental analysis confirm the 1 : 1 stoichiometry for Mn(II), Cu(II) and Zn(II) complexes whiles other metals form 1 : 2 complexes. Magnetic, electronic and IR spectral information suggest that Mn(II), Cu(II), Pd(II), Ni(II) and Co(II) exhibit planar geometry while Fe(II) and Mo(VI) crystallise with octahedral geometry. The tetrahedral environment is suggested for the Zn(ll) complex.